A new species of Eupasiphae Wood-Mason & Alcock, 1893 (Crustacea, Decapoda, Pasiphaeidae) from the southwestern Atlantic - Rodrigues, Thaiana G. A.; Cardoso, Irene A. (Zootaxa, 2018)
The pasiphaeid shrimp genus Eupasiphae Wood-Mason & Alcock, 1893 (Caridea: Pasiphaeidae) currently includes four bathypelagic species: Eupasiphae latirostris (Wood-Mason, 1891), E. gilesii (Wood-Mason, 1892), E. serrata Rathbun, 1902 and E. paucidentata Crosnier, 1988. The present work describes a further new species, Eupasiphae ostrovski n. sp., on the basis of material sampled at the continental shelf and slope of the Central Brazilian coast at depths of 200 – 2000 m. The new species is somewhat similar to E. paucidentata, only known from Madagascar, but can be easily distinguished from all other congeneric species by the number and shape of lateral carinae at carapace and by the middorsal carina of the carapace being without teeth anteriorly and with 0–3 posteriorly. The new species is the first Eupasiphae representative known from the southwestern Atlantic.